The development of an online-based TPACK questionnaire for ELT teachers - Surayya, ST Ayu; Asrobi, Maman; Maysuroh, Siti; Farizi, Zukhruf (Englisia: Journal of Language, Education, and Humanities, 2023)
The concept of Technological Pedagogical Content Knowledge (TPACK) has gained significant attention in the field of education due to the widespread adoption of innovative technologies, particularly accelerated by the COVID-19 pandemic and the surge in online teaching. To effectively measure TPACK, the utilization of a well-designed and tailored questionnaire has emerged as a sophisticated approach. The aim of this research is to develop a questionnaire that is valid and reliable specifically for the context of online learning. In order to ensure the validity of the questionnaire, expert validation was conducted with three professionals from diverse backgrounds, including an Indonesian professor, a Ph.D. student, and a local education supervisor. By incorporating their recommendations, the questionnaire underwent revisions and refinements. Subsequently, the validity of the questionnaire was assessed by administering it to 43 participants across four Indonesian provinces: West Java, East Java, East Boneo, and West Nusa Tenggara. The findings indicated that the questionnaire demonstrated strong validity and reliability, making it a valuable tool for evaluating teachers' TPACK in online teaching environments. Statistical analysis using the SPSS 23.0 software confirmed the validity and reliability of all 24 questionnaire items, further endorsing its readiness for future research endeavors. Additionally, this questionnaire can be tailored to meet the unique requirements of teachers across different education programs, thereby enhancing its applicability and versatility. In conclusion, this study contributes to the field of online teaching by providing a robust instrument for assessing teachers' TPACK, facilitating targeted interventions and improvements in instructional practices.